PKM Peningkatan Produktivitas Usaha Pdam Mual Nauli Melalui Upgrading Kompetensi Sumberdaya Manusia (SDM) Berstandar Layanan Prima (Sibuluan Raya, Kec. Pandan, Kabupaten Tapanuli Tengah, Sumatera Utara - Rizki Syahputra; Rini Indahwati; Ilham Hidayah Napitupulu; Ing Heru Pranoto (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2024)
The Community Service Program is carried out in collaboration with PDAM Mual Nauli, Tapanuli Tengah, as proposed under the Memorandum of Understanding (MOU) between the State Polytechnic of Medan and the Government of Sibolga City. It also serves as the realization of the Community Service Program that supports the accreditation excellence for the Master of Applied Accounting Information Systems (MTSIA) program. The purpose of this activity is to assist PDAM Mual Nauli in addressing specific challenges, particularly related to human resources and public services as a water supply company in the region. The specific objectives of this Community Service Program are to provide solutions in the areas of management, human resource management, and the improvement of production quality in public service delivery to the water users of PDAM Mual Nauli. The method in implementing this community service activity involves stages such as surveys, interviews, observations, and confirmation with PDAM Mual Nauli as the partner. The interviews are conducted by the Community Service Team at the PDAM Mual Nauli office. After obtaining the data, analysis is carried out and explained in a descriptive form with explanations supported by graphic information, tables, and other relevant elements. The three activities implemented at PDAM Mual Nauli include public speaking training, internal control training, and financial reporting training. These training activities aim to enhance the quality of human resources, especially in public services. Keywords: Drinking Water, Public Services, Human Resources Quality